Assessment of drinking water quality supplied to primary schools: A case study of Ballia city, Uttar Pradesh - Kamlesh Verma,; Vinay Kumar Rai, (National Geographical Journal of India, 2021)
Massive urbanization and industrialization are playing a catalytic role in increasing water demand which leads to fast extraction and contamination of drinking water. The process of rapid urbanization is creating serious challenges related to proper water supply with quality and quantity. The research aims to assess the quality of drinking water supplied to primary schools of different wards in Ballia city. Water samples to test the quality of drinking water have been collected from India Mark II hand pumps from different wards. These water samples have been tested in the laboratory and data are tabulated, analyzed in excel software. Distribution maps are prepared with the help of Arc GIS. This study reveals that the pH level of the entire city is good but TDS is above the permissible limit at some primary schools i.e. Neuri (599 mg/l) and Vijayipur (542 mg/l). The concentration of hardness, alkalinity and calcium are above the permissible level of BIS standard while the concentration of magnesium and Sulphate is below the permissible limit of BIS in all primary schools.